A Study of Anti-Radiation Weaving Fabric with Plasma Corona Treatment - Valentinus Galih Vidia Putra; Irwan Irwan; Ichsan Purnama; Juliany Ningsih Mohamad; Yusril Yusuf (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2021)
In this research, Carbon black particles were applied on the woven fabric by the knife coating technique and pretreatment using plasma corona discharge to build-up conductive cotton-polyester (CVC 50%) fabric electromagnetic shielding material. This paper describes the making of anti-radiation weaving fabric using plasma technology. The anti-radiation patch was developed by first modifying the textile fabric's surface using atmospheric pressure plasma technology using tip-cylinder electrode configuration. The plasma corona discharge was generated using high voltage electricity with asymmetrical electrodes (tip and cylinder). The treated weaving fabric using plasma was then coated with carbon black ink. This research indicates that an anti-radiation weaving fabric was successfully shielded electromagnetic radiation from an electronic device.